1997
DOI: 10.1038/bjc.1997.306
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of plasminogen activators and their inhibitors to the survival prognosis of patients with Dukes' stage B and C colorectal cancer

Abstract: Summary Despite the advances in pre-, peri-and post-operative medical care of colorectal carcinoma patients, the prognosis has improved only marginally over recent decades. Thus, additional prognostic indicators would be of great clinical value to select patients for adjuvant therapy. In previous studies we found that colorectal carcinomas have a marked increase of the urokinase-type of plasminogen activator (u-PA), and the inhibitors PAI-1 and PAI-2, whereas the tissue-type plasminogen activator (t-PA) is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Furthermore, uPA and uPAR expression were more intensive and more frequent in Dukes C/B than in Dukes A tumors [13,17], indicating that the proteins were associated with tumor progression. A positive association was found between survival of patients with Dukes B or C colorectal cancer and epithelial uPA or uPAR staining [18,19]. The uPA and uPAR appear to be strong prognostic markers for patients with CRC and their value to predict metastasis (liver metastasis), disease recurrence and overall survival has been documented [5,10,14].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, uPA and uPAR expression were more intensive and more frequent in Dukes C/B than in Dukes A tumors [13,17], indicating that the proteins were associated with tumor progression. A positive association was found between survival of patients with Dukes B or C colorectal cancer and epithelial uPA or uPAR staining [18,19]. The uPA and uPAR appear to be strong prognostic markers for patients with CRC and their value to predict metastasis (liver metastasis), disease recurrence and overall survival has been documented [5,10,14].…”
Section: Discussionmentioning
confidence: 91%
“…As reported in the scientific literature, the increased levels of tissue and circulating PAI-1 would not significantly inhibit plasminogen activators activity in primary tumors, so that the balance will favor proteolysis, and PAI-1 serum and tissue levels negatively influence prognosis and overall and disease-free survival in breast, bladder, ovarian, lung, gastric, and colorectal cancer patients (Sakakibara et al 2006;Beyer et al 2006;Offersen et al 2007;Speleman et al 2007). In colorectal cancer patients, even several plasminogen activation parameters in normal colorectal mucosa are of prognostic relevance for the overall survival of the patients (Ganesh et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Some of the studies discussed above also showed that cathepsins or some PAs also have a prognostic significance for patients with CRC; 23,24,30 however, to our knowledge, cysteine and serine proteases have not been evaluated in the same experimental setting, and the prognostic relevance of cathepsins in CRC has not been compared with that of UPA, TPA, and PAI-1. Therefore, the objective of the current study was to measure the tissue antigen concentrations of cysteine proteases (CATB and CATL), serine proteases (UPA and TPA), and their inhibitor (PAI-1) in the same patients, in CRC tissue (CANCER), and in its normal counterpart (NORMAL) obtained from a tumor free area and, then, to evaluate any correlation between these parameters and the major histomorphologic and prognostic parameters of CRC.…”
mentioning
confidence: 99%
“…16 -20 In the specific case of colorectal carcinoma (CRC), several studies have been also published on tissue cathepsins 21,22 and the PA system. [23][24][25][26] Immunohistochemical studies have shown intensive staining with antibodies against CATB, UPA, and PAI-1 in CRC, particularly at sites of invasive growth. [27][28][29][30][31] The correlations between cysteine and serine proteases and tumor invasion and metastases also have been confirmed by several in vitro studies, which demonstrated that increased protease levels correlate with the invasive and metastatic potential of malignant tumors.…”
mentioning
confidence: 99%